Theory and Application of Reuse, Integration, and Data Science - Bouabana-Tebibel, Thouraya; Bouzar-Benlabiod, Lydia; Rubin, Stuart H. (Advances in Intelligent Systems and Computing, 2019)
This book presents recent research in the field of reuse and integration, and will help researchers and practitioners alike to understand how they can implement reuse in different stages of software development and in various domains, from robotics and security authentication to environmental issues. Indeed, reuse is not only confined to reusing code; it can be included in every software development step. The challenge today is more about adapting solutions from one language to another, or from one domain to another. The relative validation of the reused artifacts in their new environment is also necessary, at time even critical. The book includes high-quality research papers on these and many other aspects, written by experts in information reuse and integration, who cover the latest advances in the field. Their contributions are extended versions of the best papers presented at the IEEE International Conference on Information Reuse and Integration (IRI) and IEEE International Workshop on Formal Methods Integration (FMI), which were held in San Diego in August 2017.